Flexural capacity and crack-closing performance of NiTi and NiTiNb shape-memory alloy fibers randomly distributed in mortar beams. (15th November 2018) - Lee, Jong-Han; Lee, Kun-Joon; Choi, Eunsoo
Abstract: This study assesses the flexural capacity of cement mortar beams that are randomly reinforced with discrete NiTi and NiTiNb shape-memory alloy (SMA) fibers. To achieve this goal, material tests were first performed to analyze the element components and the thermal and mechanical properties of the SMA fibers. The phase change temperature to the austenite was designed to be around 100 °C without damaging the mortar matrix during the heating process. Using fiber volume fractions of 0.50, 0.75, and 1.00%, four-point bending tests were performed with beam specimens that have 40 ✕ 40 mm 2 square cross-section with a length of 160 mm. The cracking and post-cracking strengths and the energy absorption capacity were mainly dependent on the mechanical properties and content of SMA fibers. Based on the flexural strength and energy absorption capacity, an equivalent flexural strength ratio that is used in the flexural design of fiber-reinforced cement composites can be proposed to account for the improvement of the ductility in the SMA fiber-reinforced beams. Additionally, this study evaluates the crack-closing performance induced by the activation of the shape memory effect of SMA fibers. The amount of the closed flexural cracks increased with increasing fiber content and depended on the recovery performance of the fiber. The linear trend analysis shows that the crack-closing stress can be generated by approximately 0.36 and 0.06 MPa per 1.00% increase in NiTi and NiTiNb fibers in cement composite beams, respectively.